2008
DOI: 10.1111/j.1349-7006.2007.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms of the base excision repair gene MUTYH and increased colorectal cancer risk in a Japanese population

Abstract: The MUTYH gene encodes a DNA glycosylase that can initiate the base excision repair pathway and prevent G:C > > > > T:A transversion by excising adenine mispaired with 8-hydroxyguanine. Biallelic germline mutations of MUTYH have been shown to predict familial and sporadic multiple colorectal adenomas and carcinomas, however, whether there is an association between single nucleotide polymorphisms (SNPs) of MUTYH and sporadic colorectal cancer (CRC) risk has remained unclear. In this study we investigated four M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…However, there have also been genetic studies that suggest an increased risk for CRC and lung cancer associated with the Q324H variant [139-142]. Analysis of the adenine glycosylase activity of Q324H MUTYH indicated a slightly reduced activity, similar to that observed with G382D MUTYH.…”
Section: Mutyh-associated Polyposismentioning
confidence: 83%
“…However, there have also been genetic studies that suggest an increased risk for CRC and lung cancer associated with the Q324H variant [139-142]. Analysis of the adenine glycosylase activity of Q324H MUTYH indicated a slightly reduced activity, similar to that observed with G382D MUTYH.…”
Section: Mutyh-associated Polyposismentioning
confidence: 83%
“…An example of one common SNP in the MUTYH gene is the nonsynonymous Gln335His variation in codon 12 (49,50). The enzyme encoded by this variant has been demonstrated to have partially impaired glycosylase activity in vitro , and could therefore contribute to cancer susceptibility, being much more frequently detected in Japanese and Chinese populations than in European populations (34,52). The Gln335His variant allele has been suggested to be associated with increased risk of colorectal cancer (50,52,57) and less consistently with lung cancer (53).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme encoded by this variant has been demonstrated to have partially impaired glycosylase activity in vitro , and could therefore contribute to cancer susceptibility, being much more frequently detected in Japanese and Chinese populations than in European populations (34,52). The Gln335His variant allele has been suggested to be associated with increased risk of colorectal cancer (50,52,57) and less consistently with lung cancer (53). For the latter, however, existing evidence is conflicting or significant only when taking into account gene-gene interactions (53).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene result in a heritable predisposition to colon and stomach cancers (Tsuzuki et al, 2007). Tao et al (2008) studied the association between genetic polymorphisms of MUTYH gene and increased CRC risk. They investigated four MUTYH SNPs, IVS1+11C>T, IVS6+35G>A, IVS10-2A>G, and 972G>C, for association with increased CRC risk in a population based series of 685 CRC patients and 778 control subjects from Kyushu, Japan.…”
Section: Mutyh Genementioning
confidence: 99%
“…This polymorphism occurs in the region between exon 1 and intron 1 of MUTYH gene. Also, to investigate the association of MUTYH G 13638 C and APEX1 T6865G with CRC and smoking in a Japanese population (Tao et al, 2008), Kasahara et al (2008) conducted a study. In this study the genetic polymorphisms of DNA repair enzymes MUTYH G 13638 C and APEX1 T6865G were determined using PCR-RFLP and results showed that the MUTYH G 13638 C is strongly associated with CRC susceptibility.…”
Section: Mutyh Genementioning
confidence: 99%